2023
DOI: 10.3390/ijerph20043149
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure to Pesticides as a Risk Factor for Sleep Disorders

Abstract: Inadequate sleep has been linked to a variety of impairments in bodily functions, including endocrine, metabolic, higher cortical function, and neurological disorders. For this reason, the aim of this study was to analyze the link between occupational pesticide exposure and sleep health among farmers in Almeria. A cross-sectional study was conducted among a population living on the coast of Almeria (southeastern Spain), where about 33,321 hectares of land are used for intensive agriculture in plastic greenhous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
0
4
0
1
Order By: Relevance
“…Several studies have been carried out to determine the effects of pesticides on neurological illnesses. Alzheimer's disease and Parkinson's disease are the most common disorders connected to pesticide neurotoxicity [ 143 , 144 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have been carried out to determine the effects of pesticides on neurological illnesses. Alzheimer's disease and Parkinson's disease are the most common disorders connected to pesticide neurotoxicity [ 143 , 144 ].…”
Section: Resultsmentioning
confidence: 99%
“…Farmers from three agricultural areas (La Ceniza, Chichihualco and Quechultenango), 90 to 99% did not use personal protective equipment (PPE) when applying the pesticide, and therefore had the highest prevalence of acute poisoning 61.54%, 18.45% and 21.0% respectively; Other authors such as Evaristo et al (2022), in their research, report that 32.5% of farmers in the southern region of Brazil do not use PPE due to the excessive heat it causes and 21.5% reported having suffered pesticide poisoning. Zheng et al (2023) al (2021) points out that the low use of PPE is mainly due to farmers' lack of awareness, availability and high cost, and the discomfort they experience when using it due to the heat. Of the areas studied, farmers in the community of La Ceniza had the highest prevalence of Acute Pesticide Intoxication (IAP), this is possibly due to the fact that 92.3% of these farmers do not use personal protective equipment and it is the community where A greater variety of pesticides are used (14 different pesticides), and the application is also carried out against the wind (12%); They do not respect the re-entry time to the crop since they return to the fumigated crop in three days on average, and 62% of farmers mix or combine pesticides when applying them; Therefore, the toxicity of the product increases.…”
Section: Discussionmentioning
confidence: 99%
“…Higher levels of these metals in human bodies make individuals more susceptible to sleep disorders ( 17 , 54 , 60 , 61 ). Additionally, exposure to certain pesticides has been associated with difficulty falling asleep, frequent night awakenings, and decreased overall sleep quality ( 19 , 62–64 ). This study focused on the correlation between urinary PAH metabolites with self-reported sleep problems and SSD.…”
Section: Discussionmentioning
confidence: 99%